2018
DOI: 10.1177/2151459318808845
|View full text |Cite
|
Sign up to set email alerts
|

Admitting Service Affects Cost and Length of Stay of Hip Fracture Patients

Abstract: Introduction:The purpose of this study was to analyze the effect of the admitting service on cost of care for hip fracture patients by comparing the cost difference between patients admitted to the medicine service versus those admitted to a surgical service.Methods:A 2-year cohort of patients 55 years or older who were admitted to a single level 1 trauma center with an operative hip fracture were included. Patient demographics, comorbidities, admitting service, complications, and hospital length of stay were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 12 publications
0
12
1
Order By: Relevance
“…3,4 Without surgery, the reported mortality rate has been shown to increase to 84.4%. 5 Surgical treatment is an expensive endeavor, with Lott et al 6 demonstrating an average cost of approximately $30,000 for operative hip fracture treatment at their urban safety-net hospital. Even with expensive surgery, morbidity in the surviving population is high, with significant loss of function and decreased ability to live independently.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Without surgery, the reported mortality rate has been shown to increase to 84.4%. 5 Surgical treatment is an expensive endeavor, with Lott et al 6 demonstrating an average cost of approximately $30,000 for operative hip fracture treatment at their urban safety-net hospital. Even with expensive surgery, morbidity in the surviving population is high, with significant loss of function and decreased ability to live independently.…”
Section: Introductionmentioning
confidence: 99%
“… 7 , 8 Although implementations such as orthogeriatric comanagement programs have been shown to decrease LOS and lower inpatient hospitalization cost, geriatric hip fractures still continue to be a disproportionately large resource consumer: hip fractures represent only 14% of geriatric fractures, yet they account for approximately 72% of the total costs of care. 9 10 11 12 Garcia et al 9 found the American Society of Anesthesiologist's (ASA) classification, a measure of the sum of a patient's comorbidities, to have the strongest association with increased LOS in this population. Each increase in ASA classification added an extra $9300 to the daily hospital stay.…”
mentioning
confidence: 99%
“…Focus on preoperative optimization, surgical techniques, and pain control have been integral in improving a patient's LOS. 20,21 However, an additional clinical consideration should be the improvement of perioperative patient care, like neuraxial anesthesia. In our study, patients receiving mepivacaine stayed almost 10 hours less and were 10 times more likely to be discharged home on POD 0 than patients who had bupivacaine.…”
Section: Discussionmentioning
confidence: 99%